Energy Consumption Evaluation for Wireless Sensor Network Nodes Based on Queuing Petri Net. (23rd April 2014) - Li, J.; Zhou, H. Y.; Zuo, D. C.; Hou, K. M.; Xie, H. P.; Zhou, P.
Abstract : Due to the large scale of wireless sensor networks (WSN) and the huge density of WSN nodes, classical performance evaluation techniques face new challenges in view of the complexity and diversity in WSN applications. This paper presents a "state-event-transition" formal description for WSN nodes and proposes an event-drivenQPN -based modeling technique to simulate the energy behaviors of nodes. Besides, the framework architecture of a dedicated energy evaluation platform has been introduced, which can be used to simulate the energy consumption of WSN nodes and to evaluate the system lifetime of WSN. Case studies prove that this platform can be utilized for the selection of WSN nodes and network protocols, the deployment of network topology, and the prediction of system lifetime as well.